If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2x-68=x-5
We move all terms to the left:
2x-68-(x-5)=0
We get rid of parentheses
2x-x+5-68=0
We add all the numbers together, and all the variables
x-63=0
We move all terms containing x to the left, all other terms to the right
x=63
| x/4+30=x | | 40,000=4^x | | -312+5t=572 | | 5c-61=2c-4 | | 4x-120=-4x+6 | | 40,000=1(4)^x | | 3v+3=2v+82 | | x+3x+180+1.5x=456 | | s+70=s | | 4x+1+1+1=9 | | 40x+30=145 | | 18–−x=–7 | | 2c+24=c | | -3|2p-5|=-15 | | 6-3(2x-4)=-42 | | 5y-72=y | | 2x+1/4+1/4=4 | | 8(k+4)=–88 | | 10m+5+3m=2(m-3) | | 3f–4f=17 | | e3=1728 | | 3n-5=-8(,6+5n) | | 3.5=(2x÷3)-1 | | 8^x+3=16^2x+1 | | 2(x+1)-1=4x-2(2+x) | | 5x-2-4x+10/5=2/4 | | 5w+9=2w+24 | | 2x+1+6x=3x+51 | | 4(y-10)=6(y+12) | | x(4X-15)=1 | | 3x+5=3x^2+5x | | 6x-2=8x+20 |